2016
DOI: 10.2337/dc15-2688
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin Enhances Fat Oxidation and Ketone Production in Patients With Type 2 Diabetes

Abstract: OBJECTIVEInsulin resistance is associated with mitochondrial dysfunction and decreased ATP synthesis. Treatment of individuals with type 2 diabetes mellitus (T2DM) with sodium–glucose transporter 2 inhibitors (SGLT2i) improves insulin sensitivity. However, recent reports have demonstrated development of ketoacidosis in subjects with T2DM treated with SGLT2i. The current study examined the effect of improved insulin sensitivity with dapagliflozin on 1) mitochondrial ATP synthesis and 2) substrate oxidation rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
151
4
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(172 citation statements)
references
References 30 publications
12
151
4
5
Order By: Relevance
“…In addition to lowering plasma glucose concentration, SGLT2 inhibitors exert multiple other metabolic actions in T2DM individuals . They improve insulin sensitivity and beta cell function, stimulate an increase in basal rate of hepatic glucose production, lower fasting plasma insulin (FPI) concentration, stimulate glucagon secretion and switch fuel consumption from glucose to fat oxidation . Some of these metabolic actions of SGLT2 inhibitors can affect ketone production in T2DM patients.…”
Section: Introductionsupporting
confidence: 91%
“…In addition to lowering plasma glucose concentration, SGLT2 inhibitors exert multiple other metabolic actions in T2DM individuals . They improve insulin sensitivity and beta cell function, stimulate an increase in basal rate of hepatic glucose production, lower fasting plasma insulin (FPI) concentration, stimulate glucagon secretion and switch fuel consumption from glucose to fat oxidation . Some of these metabolic actions of SGLT2 inhibitors can affect ketone production in T2DM patients.…”
Section: Introductionsupporting
confidence: 91%
“…Thus, we could hypothesize only concerning the potential mechanism(s) by which pioglitazone prevents an increase in plasma ketone concentration (Figure ). Previous studies from our group and others have demonstrated an increase in plasma FFA concentration and total body fat oxidation following initiation of SGLT2i therapy.…”
Section: Discussionmentioning
confidence: 53%
“…We and others have shown that, in addition to lowering plasma glucose concentration, SGLT2i exert multiple other metabolic actions in T2DM patients including improved insulin sensitivity, enhanced beta cell function, and increased plasma free fatty acid (FFA) concentration, total body fat oxidation and ketone production. Although, in absolute terms, the increase in plasma ketone concentration is small, from approximately 0.2 mM to approximately 0.4 mM, it occurs in the vast majority (>90%) of patients receiving SGLT2i therapy,, and in 10% to 20% of patients the plasma ketone level exceeds the upper limit of the normal range .…”
Section: Introductionmentioning
confidence: 99%
“…This was associated with a 116% increase in ketone bodies and a 49% increase in free fatty acids,90 demonstrating the increased lipid catabolism seen in human beings with prolonged SGLT2 inhibitor use 91. This shift from glucose to fat oxidation has also been demonstrated in patients on dapagliflozin after only 2 weeks,92 and this likely accounts for the small changes seen in lipid levels.…”
Section: Methodsmentioning
confidence: 89%